(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we offer an explanation to pension systems cyclical reforms, based on Central East Europe (CEE) countries experience over the last three decades. We claim that in the transition to funded pension design, the government not only transfers longevity and fiscal risks to the individualbut also absorbs risks transferred from the public, where each market actor transfers undiversifiable risks to the other. This hidden risk path that has not been discussed yet in the literature, stemmed from the public expectation to risk premium or adequate old age benefits that evolves to political pressure. The outcomes of this risk path realized in financial transfers, such as social security, means-tested and minimum pension guarantee. Consequently, funded pension designs naturally converge to a new landscape paradigm of risk sharing, including intergenerational and intra-generational play. Financial crises such as the recent COVID-19 pandemic foster the convergence process.